1233 Estimating the prevalence of occupational exposure in lung cancer. results from an hospital-based case-series in italy. (24th April 2018) - Bonzini, M; Bordini, L; Paticchia, V; Zucca, I; Bareggi, C; Palleschi, A; Consonni, D; Pesatori, AC; Riboldi, L
Abstract : Introduction: Lung cancer (LC) is the leading oncologic cause of death among males. The role of occupational history with exposure to well-established carcinogens is very important, but usually deeply underestimated. To undervalue the occupational origin of cancer can affect the efficacy of preventive measures and preclude patients to receive insurance benefits. We performed a systematic occupational medicine evaluation of a cases-series of lung cancer cases to properly quantify the proportion of LC cases with previous occupational exposure to carcinogens. Methods: We systematically evaluated all consecutive LC cases hospitalised in a large university hospital, in Milan. An active systematic search was carried out for 24 months, by trained occupational physicians, using a standardised questionnaire. Results: We collected 123 consecutive LC cases (66% males). Former and current smoking habit was found in 61% and 22%, respectively. A clear exposure to occupational carcinogens (in details: asbestos, polycyclic aromatic hydrocarbons, paintings, diesel exhaust) was recognised in 10% of males cases. Discussion: Previous occupational exposure to carcinogens was frequent among males cases in Northern Italy. The observed prevalence was even lower than the one reported in a previous systematic search in Lombardy (Porru S, et al. Int Arch Occ Env Health 89:981–9). If we applied our observed proportion of occupational cases to the entire incident LC cases in Lombardy population, we should observe about 460 male occupational LC cases per year (AIRTUM-AIOM report 2016), actually more than the entire number of cancer (all sites, both gender) annually notified to National Institute for Insurance (INAIL Rapporto regionale 2015).